Administrative empowerment and its relationship to the organizational commitment of middle school assistants in Wasit Governorate, Iraq, from their point of view - Radhawi, Saad Naeem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the level of both administrative empowerment and organizational commitment of middle school assistants in Wasit Governorate, Iraq, and the relationship between them from their point of view, and the research adopted the relational, descriptive approach. The study tool consisted of a questionnaire of (29) items, which were distributed to a random sample of (80) assistants in middle schools affiliated to the General Directorate of Education in Wasit Governorate. The results of the research data were analyzed using the (SPSS) program. The results of the research showed that the level of administrative empowerment of middle school assistants obtained an overall average (3.38 out of 5) with a rating of (good). This result reflects the presence of a positive trend towards administrative empowerment within the school. After participating in decision-making an average of (3.62), then after the mandate, an average was obtained (3.15), and the organizational commitment obtained an overall average (3.92 out of 5) with a rating of (good) among the sample members, and at the level of dimensions, after the responsibility towards work, an average was obtained (4.26) After the desire to continue working on average (3.59), as well as the existence of a statistically significant correlational relationship between the administrative empowerment of service assistants and the level of organizational commitment, it reached (0.65) with a rating of (medium) and based on the research results, the researcher presented a set of recommendations and proposals for expansion in Administrative empowerment in a way that raises the organizational commitment of middle school assistants in Wasit Governorate, all of Iraq and Arab countries.
Keywords: Administrative Empowerment; Organizational Commitment; Associates; Middle Schools; Wasit Governorate